Assesment of the industry competitiveness of the Baltic States in the EU during the period of economic recession - Remeikiene, Rita; Startiene, Grazina; Dumciuviene, Daiva (Technological and Economic Development of Economy, 2015)
The purpose of the article is to carry out the assessment of the industrial competitiveness of the Baltic States in the EU during the period of economic recession. Revealed comparative advantage (RCA) and Symmetric index (SI) index values revealed that after the period of economic recession, the growth of the industrial competitiveness of the Baltic States, considering it from export positions, is slower in comparison with GDP changes. Latvia has taken strong competitive positions in the industry of raw materials; Estonia also has medium comparative advantage in the industry of raw materials, while Lithuania has the comparative advantage in the industries of mineral fuels, lubricants and related materials. Export competitiveness index (XCI) results showed that all three Baltic States had growing competitive advantage in the industries of food, drinks and tobacco during both the period of economic recession and the period of economic revival. In the period of economic revival Estonia showed the growth potential in the industries of chemicals and related products, while Lithuania – in the industry of raw materials and related products.The identification of competitive industries during the periods of economic recession and revival can provide the governments of the Baltic States with the target data not only for supporting export companies, but also for taking the best decisions to improve the business environment in the industries that have the competitive advantage.